Parametric Analysis of the Defected Ground Structure-Based Hairpin Band Pass Filter for VSAT System on Chip Applications - Ambati, N.; Immadi, G.; Narayana, M. V.; Bareddy, K. R.; Prapurna, M. S.; Yanapu, J. (Engineering, Technology & Applied Science Research, 2021)
In this study, a three-pole hairpin structure was fabricated on the top of the substrate material and an open loop microstrip structure at the ground to give a modified triple-band BPF with a unique design. A Rogers (RT5880) material with εr = 2.2 and thickness of 1.27mm was used to fabricate the proposed structure. The space between two consecutive hairpin resonators has different distances d1 and d2 with values of 0.2mm and 0.4mm respectively. The proposed filter offers a compact size with low return loss. The equivalent LC circuit of the DGS and hairpin structure is obtained with the Ansys electronic desktop and by using simple circuit analysis. The desired microstrip triple-band BPF operates at the Ku band, resonates at 10.28GHz, 12GHz, and 14.62GHz, while the simulated and experimental results are almost identical. The proposed wideband BPF satisfies the International Telecommunication Union ((ITU) region 3 spectrum requirements. Direct Broadcast Service (DBS) and Fixed Satellite Service (FSS) in transmit mode respectively employ the frequency band 11.41-12.92GHz and 14-14.5GHz.